MEMPREDIKSI PERUSAHAAN YANG BERPOTENSI MENGALAMI MASALAH KEUANGAN DENGAN MODEL ALTMAN, SPRINGATE, DAN ZMIJEWSKI (Studi pada Perusahaan Ritel yang Terdaftar di BEI Periode Tahun 2012-2016) - Nilasari, Devy; Haryanto, Mulyo (Diponegoro Journal of Management, 2018)
National retail sales in the period of January-June 2017 experienced a slowdown compared to the same period the previous year (YoY). Nielsen Retail Audit data show that national retail sales in the first half of this year only grew 3.7 percent from 10.2 percent. This study purpose to find out the prediction model of Financial Distress that is most suitable for its application in Retail companies in Indonesia. This study compares three models of financial distress prediction there are the model of  Altman, Springate, and Zmijewski by analyzing the accuracy of each model. The model with the highest accuracy is used to predict Retail companies that will experience financial distress in the future. The research data is taken from the financial statements of Retail companies listed in Indonesia Stock Exchange (IDX) for the period 2012-2016. The samples used in this study as many as 12 companies by using purposive sampling technique. The method of analysis used is logistic regression. The  results  showed  if  the  Altman  and  Zmijewski  models  can  be  used  to  predict financial distress in Retail companies. The most accurate model is the Zmijewski model. At the end of the research model Zmijewski used to predict 12 companies Retail listed on the IDX  period  2016.  The  prediction  results show  that  three  companies are  predicted  to experience financial distress in the future.